2020
DOI: 10.1186/s12906-020-2839-3
|View full text |Cite
|
Sign up to set email alerts
|

Lirioresinol B dimethyl ether inhibits NF-κB and COX-2 and activates IκBα expression in CCl4-induced hepatic fibrosis

Abstract: Background: Inflammation is one of the key components in the initiation and progression of hepatic diseases. If not treated, inflammation may cause cell dysplasia, and ultimately cancer. In the current study, we investigated the anti-inflammatory and anti-cancer activities of plant isolated compound Lirioresinol B Dimethyl Ether (LBDE) extracted from the seeds of Magnolia fargesii CHENG (Magnoliaceae) against HepG2 cells as well as in BALB/C male mice. Methods: We assessed the antioxidant and anti-proliferativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Fraction E also provides cytotoxic activity, although it was not efficacious than fraction B. This activity might be affected by NF- κ B signaling pathway inhibition [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fraction E also provides cytotoxic activity, although it was not efficacious than fraction B. This activity might be affected by NF- κ B signaling pathway inhibition [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The current investigation showed that the pro-inflammatory signaling of NF-κB activation and COX2 were significantly upregulated in SHR rats. NF-κB regulates inflammatory cytokine production via the COX2 pathway, which is critical in mediating fibrosis [ 38 , 39 ]. Stress-induced cardiac remodeling (physiological and pathological hypertrophy), permanent functional impairment, and heart failure are the consequences of prolonged cellular adaptation [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that CCl 4 toxicity can trigger the recruitment inflammatory mediators, such as TNF- α , IL-1 β , IL-6, Cox2, and iNOS, thereby inducing liver inflammation [ 46 ]. TNF- α , IL-1 β , and IL-6 mainly contribute to HSCs activation; Cox2 and iNOS are the main regulators of the inflammatory response; Cox2 induces prostaglandin E2 (PGE2) production and then mediates inflammation in the liver disease models [ 47 ]; the continuous production of NO is associated with the increased iNOS expression. In our experiment, HJRG downregulated the expression of the proinflammatory factors (TNF- α , IL-1 β , and IL-6).…”
Section: Discussionmentioning
confidence: 99%